If everyone returned, the island would sink : urbanisation and migration in Vanuatu - Petrou, Kirstie (Pacific perspectives ;, 2020)
"Focusing on the small island of Paama, Vanuatu, and the capital, Port Vila, this book presents a rare and recent study of the ongoing significance of urbanization and internal migration in the Global South. Based on longitudinal research undertaken in rural 'home' places, urban suburbs and informal settlements, this book reveals the deep ambivalence of the outcome of migration, and argues that the fundamental organizing principles of cultural life - in this case centered on kinship and an 'island home' - are significantly more important for urban and rural living than the effects of migration"--